A Prospective Cohort Study to Determine the Incidence of IHCP and Pregnancy Outcome in Women with Cholestasis of Pregnancy Type of article - Pranjali, Dhume; Sunil, Chawla; Gunasekaran, Madhumidha; Parikh, Sameena; Suyash, Goel; Ankur, Shah (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: This study was conducted to determine the incidence and outcomes of obstetric cholestasis in pregnancy. STUDY DESIGN: This was a hospital-based, observational, prospective cohort study conducted among antenatal women in the late second trimester and third trimester (24 to 40 weeks of gestational age) attending an antenatal clinic at the Department of Obstetrics and Gynaecology, Base Hospital, Delhi Cantt, New Delhi. The study was conducted over two years, from June 2022 to November 2023, after obtaining approval from the institutional ethics committee and written informed consent from the participants. RESULTS: Most participants (96.0%) had mild intrahepatic cholestasis of pregnancy (IHCP), while 2.8% had moderate and 1.2% had severe IHCP. Gestational age at delivery significantly correlated with IHCP severity (p=0.023). Mild IHCP cases had a lower incidence of premature rupture of membranes (6.7%) compared to moderate to severe IHCP cases (20%), although the difference was not statistically significant. A significant difference was found between IHCP severity and the mode of delivery (p=0.023), with a higher proportion of term deliveries in mild IHCP cases (94.2%) compared to moderate to severe IHCP cases (70.0%). Although the occurrence of meconium staining was relatively higher among moderate to severe IHCP cases than mild IHCP cases (20% vs. 10%, respectively), the difference was not statistically significant. No significant association was observed between IHCP severity and postpartum hemorrhage (PPH). CONCLUSION: IHCP predominantly affects pregnant women under the age of 35, with most cases presenting with mild severity. Maternal complications such as premature rupture of membranes and mode of delivery were found to vary based on IHCP severity, with term deliveries being more common among mild cases.